Anthropometric Analysis of the Velopharynx and Related Craniometric Dimensions in Three Adult Populations Using MRI. (January 2016) - Perry, Jamie L.; Kuehn, David P.; Sutton, Bradley P.; Gamage, Jinadasa K.; Fang, Xiangming
Objective: The purpose of this study is to examine effects of sex, race, and craniometry among three distinct racial groups of adults with normal velopharyngeal anatomy and to determine whether craniofacial structures could be used to predict velopharyngeal structures. Methods: A total of 88 adults across three racial groups including white, black, and Asian (Japanese) participated. Magnetic resonance images were obtained using a high-resolution, three-dimensional anatomical scan. Measurements were obtained on the levator veli palatini muscle, velum, and craniofacial structures. Results: Head circumference was used as a covariate to control the effect of overall cranial size on the analyses. Palate height, linear cranial base, and face height and width vary based on sex, with men demonstrating larger values compared with women. Linear base values, cranial base angle, and face width vary significantly based on race, with Japanese subjects showing the smallest anterior to posterior measures and larger face-width values. Levator muscle measures, excluding angle measures, vary significantly ( P < .0001) based on sex. There was no statistically significant difference ( P > .05) among racial groups in the levator muscle measures. Velar length and thickness varied significantly based on race and sex. Conclusions: This is the first study to examine the interaction of race and sex on levator muscle morphology. In spite of the differences in velar dimensions, no significant differences were found in muscle size, specifically the levator veli palatini, which is contained within the velum.